Membrane electrode structure of proton exchange membrane electrolytic tank, preparation method and test system
By using gradient design method to spray the catalyst with non-uniform load distribution in the anode catalytic layer of the proton exchange membrane electrolytic cell membrane electrode, the problem of uneven structure design of the existing membrane electrode is solved and the performance of the membrane electrode is improved and cost-effective.
Patent Information
- Application Number
- CN202411692644.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
AI Technical Summary
There is a lack of clear guidance on the catalytic layer structure design of existing proton exchange membrane electrolytic cell membrane electrodes, resulting in uneven catalyst utilization and affecting the performance of membrane electrodes.
Through the gradient design method, different load catalysts are sprayed on the lower rib and the flow channel area of the membrane electrode anode catalytic layer to form a catalytic layer with non-uniform load distribution.
The catalyst utilization rate is improved, the reaction performance of the membrane electrode is improved, and the precious metal load is reduced, and the preparation cost is reduced.
Smart Images

Figure CN119481182A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode structure, a preparation method and a testing system, and in particular to a proton exchange membrane electrolyzer membrane electrode structure with non-uniform load distribution under the ribs and in the flow channel area of the anode catalyst layer, a preparation method and a testing system, belonging to the technical field of preparing proton exchange membrane electrolyzer membrane electrodes by coating methods and the field of catalytic material science. Background Art
[0002] In the context of fluctuating renewable energy input such as wind and light, hydrogen energy is not only an efficient and environmentally friendly clean energy, but also an effective way to store and consume renewable energy. Among them, proton exchange membrane water electrolysis technology has become the focus of current research because of its certain fluctuating load following ability. The performance of the membrane electrode, as the core component of the proton exchange membrane electrolyzer, directly affects the hydrogen production efficiency of the electrolyzer.
[0003] The existing preparation methods of membrane electrodes for proton exchange membrane electrolyzers tend to prepare uniform catalyst slurries, and lack clear guidance on the design of catalyst layer structures. In the prior art, such as the Chinese patent application, its application number: 202410898536.3, publication number: CN118738419A, discloses a proton exchange membrane fuel cell membrane electrode catalyst layer and its preparation method and application, which premixes a dispersion of hydroxyl-rich polysaccharide porous molecules with a catalyst and an organic solvent, and then adds a perfluorosulfonic acid electrolyte solution to fully mix to obtain a catalyst layer slurry. The hydroxyl-rich surface and hydrophobic pore structure of the polysaccharide porous molecules can enhance the apparent activity of the catalyst in the membrane electrode and improve local oxygen transport, but its hydrophobic structure affects the wettability of the catalyst layer surface to a certain extent, thereby affecting the performance of the membrane electrode. Prior art, such as a Chinese patent application, application number: 202410682569.4, publication number: CN118621340A, discloses a porous structure water electrolysis membrane electrode and a preparation method thereof, which configures a high surface tension solvent, a low surface tension solvent and an ionomer solution as a catalyst slurry, and then prepares a porous structure water electrolysis membrane electrode, improves proton conduction efficiency, accelerates water diffusion, and improves membrane electrode performance, but the porous structure will affect the mechanical stability and durability of the membrane electrode, and the parameter control of the homogenization process requires precise equipment and strict operating conditions, which is difficult to apply in practice.
[0004] The prior art lacks a clear method for adjusting the structure of the catalyst layer by adjusting the membrane electrode catalyst slurry spraying area, and tends to design the catalyst layer in a single uniform setting, but has limitations in practical applications. Therefore, clarifying a method for preparing a proton exchange membrane electrolyzer membrane electrode with non-uniform loading distribution under the ribs and in the flow channel area of the anode catalyst layer is of great significance to the field of proton exchange membrane electrolyzer membrane electrode technology. Summary of the invention
[0005] In order to solve the defects in the prior art, the present invention discloses a method, and its technical solution is as follows:
[0006] A method for preparing a membrane electrode for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region, characterized in that it comprises the following steps:
[0007] Step 1: Take 40% of the Pt / C catalyst, add ultrapure water while keeping the solid content at 1wt% and the ratio of ultrapure water / isopropanol in the solvent at 1:10. Then mix it with 30wt% of the Nafion solution according to the solid mass ratio, add isopropanol after ultrasonic mixing in an ice-water bath, and ultrasonicate it again in an ice-water bath to make the substances in the catalyst slurry evenly mixed. Place the ultrasonicated catalyst slurry in an ultrasonic crusher for multiple crushing to prevent the catalyst particles from agglomerating, and form a cathode Pt / C catalyst suspension 1;
[0008] Step 2: IrO2 and 10wt% Nafion solution are mixed according to the solid mass ratio, and the process in step 1 is repeated to form an anode IrO2 catalyst suspension 2;
[0009] Step 3: Place all the prepared slurries under magnetic stirring and wait for use;
[0010] Step 4: After cutting the proton exchange membrane Nafion115 into squares, heat-treat it in a 5wt% hydrogen peroxide solution in a water bath, and then rinse it with deionized water; heat-treat it in a 1mol / L sulfuric acid solution, and then rinse it with deionized water. Put Nafion115 into a forced air drying oven to dry it for later use, and obtain the pre-treated proton exchange membrane;
[0011] Step 5: Place the pretreated proton exchange membrane Nafion115 on the vacuum adsorption heating plate, maintain the temperature of the hot plate, and wait for the surface and internal moisture to be evaporated and the surface adsorbed flat. Place the homemade quartz mask plate on the proton exchange membrane, determine the spray center position and control the catalyst loading area, set the nitrogen carrier gas pressure, slurry spray flow rate, nozzle movement speed and other parameters, spray and deposit the Pt / C catalyst suspension 1 on one side of Nafion115, and obtain a Pt loading of 0.4 mg / cm 2 Uniform cathode catalyst layer membrane electrode;
[0012] Step 6: Turn over the membrane electrode prepared in step 5 and place it on a vacuum adsorption heating plate, repeat the operation in step 5, and continue to spray the anode with IrO2 catalyst suspension 2. Use a homemade PTFE mask plate to spray the anode catalyst layer under the ribs and flow channel in different areas to obtain an anode membrane electrode with non-uniform loading distribution in the anode catalyst layer under the ribs and flow channel areas;
[0013] Step 7: Separate the titanium fiber felt of the anode diffusion layer and the carbon paper of the cathode diffusion layer, clean them with acetone, ethanol and deionized water respectively by ultrasonic, and then put them in a blast dryer for later use;
[0014] Step 8: Use PET film for hot-pressing and plastic sealing of the membrane electrode prepared in step 6, and heat seal each side of the membrane electrode. Place the anode and cathode diffusion layers pretreated in step 7 on both sides of the anode and cathode catalyst layers of the membrane electrode after heat sealing, respectively, and place them in a metal pressing plate and put them in a hot press. Set the hot plate temperature, pressure, and holding time to obtain a proton exchange membrane electrolyzer membrane electrode with uneven loading distribution under the ribs of the anode catalyst layer and in the flow channel area.
[0015] The present invention discloses a membrane electrode structure for a proton exchange membrane electrolyzer with non-uniform loading distribution in the region under the ribs of an anode catalyst layer and in the flow channel. The structure is characterized in that a gradient design method is used to spray catalysts with different loadings in the region under the ribs and in the flow channel of the anode catalyst layer of the membrane electrode in different regions, so that the catalyst layer as a whole presents a non-uniform loading distribution to improve the membrane electrode reaction performance.
[0016] The present invention discloses a single cell performance test system, which is used to measure the membrane electrode of a proton exchange membrane electrolyzer prepared by the method of claim 2, and is characterized in that: a constant current peristaltic pump supplies deionized water from a storage tank to the anode of a membrane electrode test fixture, passes through a water heater, and then reacts on the anode side of the membrane electrode test fixture to generate oxygen, which then flows back into the storage tank. A thermal resistor is inserted into the water heater and the anode and cathode bipolar plates of the membrane electrode test fixture, and connected to a PID temperature controller to heat the water and the membrane electrode test fixture to a set temperature. At the same time, an electrochemical workstation performs electrochemical test characterization on the membrane electrode. The anode uses a titanium plate serpentine flow field, and the diffusion layer is a Freudenberg 0.25 mm thick titanium felt; the cathode uses a titanium plate serpentine flow field, and the diffusion layer is a Toray H060 carbon paper, with an effective area of 2.5×2.5 cm 2 , the peristaltic pump deionized water flow rate was 20 mL / min, the electrolytic cell temperature was 80 °C, and the polarization curve was tested by GAMRY electrochemical workstation.
[0017] The existing membrane electrode preparation process usually adopts a single uniform catalyst layer design, but there is an uneven phenomenon in the membrane electrode reaction process. The area under the catalyst layer ribs and the flow channel area have different reaction characteristics. The current density in the contact area between the catalyst layer and the gas diffusion layer is large, while the current density in the non-contact area is small. The difference in conductivity causes a difference in catalyst utilization, which further affects the performance of the membrane electrode. Therefore, it is of great significance in the field of proton exchange membrane electrolyzers to clarify a membrane electrode structure of a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel area.
[0018] Beneficial Effects
[0019] Different loading catalysts are sprayed on the rib area and flow channel area of the membrane electrode anode catalyst layer to make the catalyst layer present a non-uniform loading distribution as a whole, so as to improve the catalyst utilization rate and enhance the performance of the membrane electrode. At the same time, the non-uniform loading distribution structure is also beneficial to reduce the loading of precious metals and reduce the preparation cost.
[0020] The idea of non-uniform loading distribution in the sub-rib area and the flow channel area of the membrane electrode catalyst layer designed in the present invention can not only be used to prepare membrane electrodes for proton exchange membrane electrolyzers, but can also be used in the catalyst layer of proton exchange membrane fuel cells and other fields to deposit metal nanoparticles on both sides of the membrane to improve reaction performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the structure of a longitudinal section of a membrane electrode of a commercial proton exchange membrane electrolyzer with non-uniform loading distribution in the membrane electrode and anode catalyst layer rib and flow channel area. It is characterized in that different loading catalysts are sprayed in the membrane electrode anode catalyst layer rib area and flow channel area in different regions, so that the catalyst layer presents a non-uniform loading distribution as a whole to improve the membrane electrode reaction performance. A catalyst gradient distribution is formed to improve the membrane electrode performance.
[0022] Figure 2 The flow chart of membrane electrode preparation of the present invention is as follows: an ultrasonic sprayer is used to spray a uniform catalyst layer on the cathode side and a non-uniform catalyst layer on the anode side, and finally the Nafion 115 is hot-pressed together with the diffusion layer.
[0023] Figure 3 The diagram is a schematic diagram of the single cell performance test system. The constant current peristaltic pump supplies deionized water from the storage tank to the anode of the membrane electrode test fixture. After passing through the water heater, it reacts on the anode side of the membrane electrode test fixture to generate oxygen and flows back to the storage tank. The thermal resistor is inserted into the water heater and the anode and cathode bipolar plates of the membrane electrode test fixture, and connected to the PID temperature controller to heat the water and the membrane electrode test fixture to the set temperature. At the same time, the GAMRY electrochemical workstation performs electrochemical test characterization on the membrane electrode.
[0024] Figure 4 Schematic diagram of the single battery fixture structure.
[0025] Figure 5 This is a comparison diagram of polarization curves obtained for the membrane electrodes of Examples 1, 2, and 3 in a single cell test system under the test conditions of a cell temperature of 80° C. and a water inlet flow rate of 20 mL / min. DETAILED DESCRIPTION
[0026] In order to make the test data comparable, polarization curve tests were performed on different membrane electrodes in the same single cell fixture and under the same test conditions. The test conditions were unified as follows:
[0027] The anode uses a titanium plate serpentine flow field, and the diffusion layer is Freudenberg 0.25mm thick titanium felt; the cathode uses a titanium plate serpentine flow field, and the diffusion layer is Toray H060 carbon paper, with an effective area of 2.5×2.5cm 2 , the peristaltic pump deionized water flow rate was 20 mL / min, the electrolytic cell temperature was 80 °C, and the polarization curve was tested by GAMRY electrochemical workstation.
[0028] Embodiment 1:
[0029] Step 1: Take 40% of the Pt / C catalyst, add ultrapure water while keeping the solid content at 1wt% and the ratio of ultrapure water to isopropanol in the solvent at 1:10. Then mix it with 30wt% of the Naf ion solution at a solid mass ratio of 4:1, add isopropanol after ultrasonic mixing in an ice-water bath for 10 minutes, and ultrasonicate in an ice-water bath for another 10 minutes to make all the substances in the catalyst slurry evenly mixed. Place the ultrasonicated catalyst slurry in an ice-water bath and ultrasonicate it continuously for 3 times, each time for 10 minutes, to prevent the catalyst particles from agglomerating, and form a cathode Pt / C catalyst suspension 1;
[0030] Step 2: IrO2 and 5wt% Nafion solution were mixed at a solid mass ratio of 10:1, and the process in step 1 was repeated to form an anode IrO2 catalyst suspension 2;
[0031] Step 3: Place all the prepared slurries under magnetic stirring and wait for use;
[0032] Step 4: Cut the proton exchange membrane Nafion115 into 8×8cm 2 After the Nafion115 is cut into blocks of different sizes, it is treated in a 5wt% hydrogen peroxide solution at 80°C for 1h, then rinsed with deionized water to remove surface organic matter and impurities, and then treated in a 1mol / L sulfuric acid solution at 80°C for 1h, then rinsed with deionized water to remove surface metal impurities, and the Nafion115 is placed in a forced air drying oven at 80°C for 3h for standby use;
[0033] Step 5: Place the treated Nafion115 membrane on the vacuum adsorption heating plate of the ultrasonic spray equipment, keep the temperature of the hot plate at 90°C, and wait for the surface and internal moisture to evaporate and the surface to be adsorbed flat. Ensure that the membrane surface is flat and cover the quartz mask to determine the center position of the spraying, and ensure that the effective load area of the membrane electrode is 2.5×2.5cm 2 , set the nitrogen carrier gas pressure gauge pressure to 100pa, the slurry spraying flow rate to 1mL / min, and the nozzle moving speed to 15mm / s. Spray and deposit the Pt / C catalyst suspension 1 on one side of Nafi on115 to obtain a Pt loading of 0.4mg / cm 2 Uniform cathode catalyst layer membrane electrode;
[0034] Step 6: Turn over the membrane electrode prepared in step 5 and place it on a vacuum adsorption hot plate. Repeat the operation in step 5 to spray and deposit the IrO2 catalyst suspension 2 on the other side of Nafion115 to obtain an Ir loading of 1.5 mg / cm 2 Uniform anode catalyst layer membrane electrode;
[0035] Step 7: Cut the titanium fiber felt of the anode diffusion layer and the carbon paper of the cathode diffusion layer into 2.5×2.5 cm 2 After the blocks were cleaned with acetone, ethanol and deionized water respectively, they were put into air drying for later use;
[0036] Step 8: Use PET film for hot-pressing and plastic sealing of the membrane electrode prepared in step 6, and heat seal each side of the membrane electrode. Place the anode and cathode diffusion layers pretreated in step 7 on both sides of the anode and cathode catalyst layers of the membrane electrode prepared in step 6, respectively, and place them in a metal pressing plate and put them into a hot press. Set the hot plate temperature to 140°C, the pressure to 450kg, and the holding time to 300s to obtain a proton exchange membrane electrolyzer membrane electrode MEA-1 with the same catalyst loading in the anode catalyst layer sub-rib area and the flow channel area.
[0037] Embodiment 2:
[0038] Step 1: Take 40% of the Pt / C catalyst, add ultrapure water while keeping the solid content at 1wt% and the ratio of ultrapure water to isopropanol in the solvent at 1:10. Then mix it with 30wt% of the Naf ion solution at a solid mass ratio of 4:1, add isopropanol after ultrasonic mixing in an ice-water bath for 10 minutes, and ultrasonicate in an ice-water bath for another 10 minutes to make all the substances in the catalyst slurry evenly mixed. Place the ultrasonicated catalyst slurry in an ice-water bath and ultrasonicate it continuously for 3 times, each time for 10 minutes, to prevent the catalyst particles from agglomerating, and form a cathode Pt / C catalyst suspension 1;
[0039] Step 2: IrO2 and 5wt% Nafi on solution were mixed at a solid mass ratio of 10:1, and the process in step 1 was repeated to form an anode IrO2 catalyst suspension 2;
[0040] Step 3: Place all the prepared slurries under magnetic stirring and wait for use;
[0041] Step 4: Cut the proton exchange membrane Nafion115 into 8×8cm 2 After the Nafion115 is cut into blocks of different sizes, it is treated in a 5wt% hydrogen peroxide solution at 80°C for 1h, then rinsed with deionized water to remove surface organic matter and impurities, and then treated in a 1mol / L sulfuric acid solution at 80°C for 1h, then rinsed with deionized water to remove surface metal impurities, and the Nafion115 is placed in a forced air drying oven at 80°C for 3h for standby use;
[0042] Step 5: Place the treated Nafion115 membrane on the vacuum adsorption heating plate of the ultrasonic spray equipment, keep the temperature of the hot plate at 90°C, and wait for the surface and internal moisture to evaporate and the surface to be adsorbed flat. Ensure that the membrane surface is flat and cover the quartz mask to determine the center position of the spraying, and ensure that the effective load area of the membrane electrode is 2.5×2.5cm 2 , set the nitrogen carrier gas pressure gauge pressure to 100pa, the slurry spraying flow rate to 1mL / min, and the nozzle moving speed to 15mm / s. Spray and deposit the Pt / C catalyst suspension 1 on one side of Nafi on115 to obtain a Pt loading of 0.4mg / cm 2 Uniform cathode catalyst layer membrane electrode;
[0043] Step 6: Turn over the membrane electrode made in step 5 and place it on the vacuum adsorption heating plate, repeat the operation in step 5, and continue to spray the anode with IrO2 catalyst suspension 2. Use a homemade PTFE mask plate to spray the anode catalyst layer under the ribs and flow channels in different areas to obtain an anode Ir total loading of 1.5 mg / cm 2 And the non-uniformly loaded anodic membrane electrode corresponding to the I r loading ratio of the sub-rib region and the flow channel region is 2:1;
[0044] Step 7: Cut the titanium fiber felt of the anode diffusion layer and the carbon paper of the cathode diffusion layer into 2.5×2.5 cm 2 After the blocks were cleaned with acetone, ethanol and deionized water respectively, they were put into air drying for later use;
[0045] The pretreated anode and cathode diffusion layers in step 7 are placed on both sides of the anode and cathode catalyst layers of the membrane electrode prepared in step 6, respectively, placed in a metal pressing plate and put into a hot press, the hot plate temperature is set to 140°C, the pressure is 450kg, and the holding time is 300s to obtain a proton exchange membrane electrolyzer membrane electrode MEA-2 with a non-uniform loading distribution of the anode catalyst layer.
[0046] Embodiment 3:
[0047] Step 1: Take 40% of the Pt / C catalyst, add ultrapure water while keeping the solid content at 1wt% and the ratio of ultrapure water to isopropanol in the solvent at 1:10. Then mix it with 30wt% of the Naf ion solution at a solid mass ratio of 4:1, add isopropanol after ultrasonic mixing in an ice-water bath for 10 minutes, and ultrasonicate in an ice-water bath for another 10 minutes to make all the substances in the catalyst slurry evenly mixed. Place the ultrasonicated catalyst slurry in an ice-water bath and ultrasonicate it continuously for 3 times, each time for 10 minutes, to prevent the catalyst particles from agglomerating, and form a cathode Pt / C catalyst suspension 1;
[0048] Step 2: IrO2 and 5wt% Nafi on solution were mixed at a solid mass ratio of 10:1, and the process in step 1 was repeated to form an anode IrO2 catalyst suspension 2;
[0049] Step 3: Place all the prepared slurries under magnetic stirring and wait for use;
[0050] Step 4: Cut the proton exchange membrane Nafion115 into 8×8cm 2 After the Nafion115 is cut into blocks of different sizes, it is treated in a 5wt% hydrogen peroxide solution at 80°C for 1h, then rinsed with deionized water to remove surface organic matter and impurities, and then treated in a 1mol / L sulfuric acid solution at 80°C for 1h, then rinsed with deionized water to remove surface metal impurities, and the Nafion115 is placed in a forced air drying oven at 80°C for 3h for standby use;
[0051] Step 5: Place the treated Nafion115 membrane on the vacuum adsorption heating plate of the ultrasonic spray equipment, keep the temperature of the hot plate at 90°C, and wait for the surface and internal moisture to evaporate and the surface to be adsorbed flat. Ensure that the membrane surface is flat and cover the quartz mask to determine the center position of the spraying, and ensure that the effective load area of the membrane electrode is 2.5×2.5cm 2 , set the nitrogen carrier gas pressure gauge pressure to 100pa, the slurry spraying flow rate to 1mL / min, and the nozzle moving speed to 15mm / s. Spray and deposit the Pt / C catalyst suspension 1 on one side of Nafi on115 to obtain a Pt loading of 0.4mg / cm 2 Uniform cathode catalyst layer membrane electrode;
[0052] Step 6: Turn over the membrane electrode made in step 5 and place it on the vacuum adsorption heating plate, repeat the operation in step 5, and continue to spray the anode with IrO2 catalyst suspension 2. Use a homemade PTFE mask plate to spray the anode catalyst layer under the ribs and flow channels in different areas to obtain an anode Ir total loading of 1.5 mg / cm 2 And the non-uniformly loaded anodic membrane electrode corresponding to the I r loading ratio of the sub-rib region and the flow channel region is 3:1;
[0053] Step 7: Cut the titanium fiber felt of the anode diffusion layer and the carbon paper of the cathode diffusion layer into 2.5×2.5 cm 2 After the blocks were cleaned with acetone, ethanol and deionized water respectively, they were put into air drying for later use;
[0054] Step 8: The membrane electrode prepared in step 6 is treated with PET film by hot pressing and plastic sealing. Each side of the membrane electrode is heat sealed. The anode and cathode diffusion layers pretreated in step 7 are placed on both sides of the anode and cathode catalyst layers of the membrane electrode prepared in step 6, respectively. The membrane electrode is placed in a metal pressing plate and put into a hot press. The hot plate temperature is set to 140°C, the pressure is 450kg, and the holding time is 300s to obtain a proton exchange membrane electrolyzer membrane electrode MEA-3 with a non-uniform loading distribution of the anode catalyst layer.
[0055] The performance of MEA-1, 2, and 3 prepared in the above examples was tested, and the polarization curves obtained were compared by analysis. Figure 5 It can be seen that after the anode catalyst layer of Examples 2 and 3 is subjected to non-uniform loading distribution treatment in the sub-rib area and the flow channel area through step 6, at the same current density, compared with the catalyst layer membrane electrode with conventional uniform loading distribution, the battery voltage of Examples 2 and 3 is lower and the electrochemical performance is better. Example 3 is the best example.
[0056] like Figure 1 As shown, Figure 1 The difference between the structure of anode diffusion layer-anode catalyst layer-proton exchange membrane-cathode catalyst layer-cathode diffusion layer of the traditional membrane electrode structure shown on the left is that in order to improve the membrane electrode performance, the anode catalyst layer is subjected to a more refined gradient treatment, that is, different catalyst loadings are sprayed on the sub-rib area and the flow channel area respectively, to form an anode catalyst layer with uneven catalyst loading distribution, so as to improve the catalyst utilization rate, enhance the membrane electrode performance and reduce the preparation cost.
[0057] like Figure 2 As shown, the vacuum heating plate adsorbs the proton exchange membrane and evenly heats it to ensure a smooth membrane surface. At the same time, the catalyst slurry is broken into extremely fine droplets by the ultrasonic nozzle and blown out by N2, sprayed evenly on the surface of the proton exchange membrane, and the isopropanol solvent evaporates rapidly to form a uniform and smooth catalyst layer.
[0058] like Figure 3 As shown in the figure, in the single cell test system, a constant current peristaltic pump supplies deionized water from the storage tank to the anode of the membrane electrode test fixture, passes through the water heater, and then reacts on the anode side of the membrane electrode test fixture to generate oxygen, which then flows back to the storage tank. The thermal resistor is inserted into the water heater and the anode and cathode bipolar plates of the membrane electrode test fixture, and connected to the PID temperature controller to heat the water and the membrane electrode test fixture to the set temperature. At the same time, the electrochemical workstation performs electrochemical test characterization on the membrane electrode. The electrochemical performance of the single cell is tested using the step constant current method to obtain the polarization curve.
[0059] like Figure 4As shown, the single cell test fixture consists of an end plate, a bipolar plate, a polytetrafluoroethylene gasket and a heat-sealing film. After the prepared membrane electrode is heat-sealed, balanced and sealed, it is clamped into the titanium bipolar plate, fixed with bolts, and connected to the single cell test system for membrane electrode performance testing.
[0060] The present invention improves the proton exchange membrane spraying process to design a gradient for the membrane electrode catalyst layer, sprays different loading catalysts in the rib area and flow channel area of the membrane electrode anode catalyst layer, so that the catalyst layer as a whole presents a non-uniform loading distribution, thereby improving the catalyst utilization rate and improving the membrane electrode performance. At the same time, the non-uniform loading distribution structure is also beneficial to reduce the precious metal loading and reduce the preparation cost.
[0061] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A membrane electrode structure for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region, characterized in that: Different catalyst loadings are sprayed on the rib area and flow channel area of the membrane electrode anode catalyst layer in different areas, so that the catalyst layer as a whole presents a non-uniform loading distribution to improve the membrane electrode reaction performance, and a catalyst gradient distribution is formed to improve the membrane electrode performance.
2. A method for preparing a proton exchange membrane electrolyzer membrane electrode with non-uniform load distribution under the ribs of the anode catalyst layer and in the flow channel area, wherein the structure of the proton exchange membrane electrolyzer membrane electrode is the proton exchange membrane electrolyzer membrane electrode structure with non-uniform load distribution under the ribs of the anode catalyst layer and in the flow channel area as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Take 40% of the Pt / C catalyst, add ultrapure water while keeping the solid content at 1wt% and the ratio of ultrapure water / isopropanol in the solvent at 1:10; then mix with 30wt% of the Nafion solution according to the solid mass ratio, add isopropanol after ultrasonic mixing in an ice-water bath, and ultrasonicate in an ice-water bath again to make the substances in the catalyst slurry evenly mixed; place the catalyst slurry after ultrasonication in an ultrasonic crusher and crush it multiple times to prevent the catalyst particles from agglomerating, so as to form a cathode Pt / C catalyst suspension 1; Step 2: IrO2 and 10wt% Nafion solution are mixed according to the solid mass ratio, and the process in step 1 is repeated to form an anode IrO2 catalyst suspension 2; Step 3: Place all the prepared slurries under magnetic stirring and wait for use; Step 4: After cutting the proton exchange membrane Nafion115 into squares, heat-treat it in a 5wt% hydrogen peroxide solution in a water bath, and then rinse it with deionized water; heat-treat it in a 1mol / L sulfuric acid solution, and then rinse it with deionized water; put the Nafion115 into a blast drying oven to dry it for later use, and obtain the pretreated proton exchange membrane; Step 5: Place the pretreated proton exchange membrane Nafion115 on a vacuum adsorption heating plate, maintain the temperature of the hot plate, wait for the surface and internal moisture to be evaporated and the surface adsorbed flat; place the homemade quartz mask plate on the proton exchange membrane, determine the spray center position and control the catalyst loading area, set the nitrogen carrier gas pressure, slurry spray flow rate, and nozzle movement speed parameters, spray and deposit the Pt / C catalyst suspension 1 on one side of Nafion115, and obtain a Pt loading of 0.4 mg / cm 2 Uniform cathode catalyst layer membrane electrode; Step 6: Turn over the membrane electrode prepared in step 5 and place it on a vacuum adsorption heating plate, repeat the operation in step 5, and continue to spray the anode with IrO2 catalyst suspension 2; use a homemade PTFE mask plate to spray the anode catalyst layer under the ribs and flow channel in different areas to obtain an anode membrane electrode with non-uniform loading distribution in the anode catalyst layer under the ribs and flow channel areas; Step 7: The titanium fiber felt of the anode diffusion layer and the carbon paper of the cathode diffusion layer are cut into blocks, and after ultrasonic cleaning with acetone, ethanol and deionized water respectively, they are placed in a blast dryer for later use; Step 8: Use PET film for hot-pressing and plastic sealing of the membrane electrode prepared in step 6, and heat seal each side of the membrane electrode. Place the anode and cathode diffusion layers pretreated in step 7 on both sides of the anode and cathode catalyst layers of the membrane electrode after heat sealing, respectively, and place them in a metal pressing plate and put them in a hot press. Set the hot plate temperature, pressure, and holding time to obtain a proton exchange membrane electrolyzer membrane electrode with uneven loading distribution under the ribs of the anode catalyst layer and in the flow channel area.
3. The method for preparing a membrane electrode for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region according to claim 2, characterized in that: The step 1 further includes the following contents: mixing with 30wt% Nafion solution at a solid mass ratio of 4:1, adding isopropanol after ultrasonic mixing in an ice-water bath for 10 minutes, and ultrasonic mixing in an ice-water bath for 10 minutes again to make the substances in the catalyst slurry evenly mixed; placing the ultrasonic catalyst slurry in an ice-water bath for continuous ultrasonic crushing for 3 times, each time for 10 minutes, to prevent catalyst particles from agglomerating.
4. The method for preparing a membrane electrode for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region according to claim 2, characterized in that: The step 2 further includes the following content: mixing IrO2 and 10wt% Nafion solution at a solid mass ratio of 10:
1.
5. The method for preparing a membrane electrode for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region according to claim 2, characterized in that: The step 4 further includes the following contents: cutting the proton exchange membrane Nafion115 into 8×8 cm 2 After cutting into blocks of different sizes, they were treated in a 5wt% hydrogen peroxide solution at 80℃ for 1h, then rinsed with deionized water to remove surface organic matter and impurities, and then treated in a 1mol / L sulfuric acid solution at 80℃ for 1h, then rinsed with deionized water to remove surface metal impurities. Nafion115 was placed in an air drying oven at 80℃ for 3h and dried for use.
6. The method for preparing a membrane electrode for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region according to claim 2, characterized in that: The step 5 further includes the following contents: placing the pretreated proton exchange membrane Nafion115 on the vacuum adsorption heating plate of the ultrasonic spraying equipment, maintaining the temperature of the hot plate at 90°C, waiting for the surface and internal moisture to be evaporated and the surface adsorbed flat; ensuring that the membrane surface is flat and covered with a quartz mask to determine the spraying center position, ensuring that the membrane electrode effective load area is 2.5×2.5cm 2 , set the nitrogen carrier gas pressure gauge pressure to 100pa, the slurry spraying flow rate to 1mL / min, and the nozzle moving speed to 15mm / s.
7. The method for preparing a membrane electrode for a proton exchange membrane electrolyzer with non-uniform loading distribution under the ribs of the anode catalyst layer and in the flow channel region according to claim 2, characterized in that: The step 8 further includes the following contents: heat-sealing each side of the membrane electrode for 5 seconds, placing the anode and cathode diffusion layers pretreated in step 7 on both sides of the anode and cathode catalyst layers of the membrane electrode after heat sealing, placing them in a metal pressing plate and putting them into a hot press, setting the hot plate temperature to 140°C, the pressure to 450kg, and the holding time to 300 seconds, to obtain a proton exchange membrane electrolyzer membrane electrode with uneven load distribution under the ribs of the anode catalyst layer and in the flow channel area.
8. A single cell performance testing system, the system is used to measure the membrane electrode of a proton exchange membrane electrolyzer prepared by the method of claim 2; characterized in that: A constant-current peristaltic pump supplies deionized water from the storage tank to the anode of the membrane electrode test fixture. After passing through the water heater, deionized water reacts on the anode side of the membrane electrode test fixture to generate oxygen, which then flows back into the storage tank. A thermal resistor is inserted into the water heater and the anode and cathode bipolar plates of the membrane electrode test fixture, and connected to a PID temperature controller to heat the water and the membrane electrode test fixture to the set temperature. At the same time, the electrochemical workstation performs electrochemical test characterization on the membrane electrode. The anode uses a titanium plate serpentine flow field, and the diffusion layer is a Freudenberg 0.25mm thick titanium felt. The cathode uses a titanium plate serpentine flow field, the diffusion layer is Toray H060 carbon paper, and the effective area is 2.5×2.5cm 2 , the peristaltic pump deionized water flow rate was 20 mL / min, the electrolytic cell temperature was 80 °C, and the polarization curve was tested by GAMRY electrochemical workstation.
Citation Information
Patent Citations
Porous-structure electrolytic water membrane electrode and preparation method thereof
CN118621340A
Membrane electrode catalyst layer of proton exchange membrane fuel cell as well as preparation method and application of membrane electrode catalyst layer
CN118738419A
Cited By
Membrane electrode, preparation method and flow battery
CN120914301A
Membrane electrode, fuel cell and method for measuring mass transfer diffusion coefficient of gas in catalytic layer of fuel cell
CN120999058A